The Relationship Between Body Mass Index, Percent Body Fat, And Belly Fat With U20 Futsal Athlete Fitness - Dzulfiqar Diyananda; Yuliasih; Setiakarnawijaya, Yasep; Yuliana, Ela; Ihsani, Sri Indah (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
This study aims to determine the relationship between body mass index, body fat, and physical fitness of U20 futsal players at the Futsal Student Activity Unit (UKM) University of Indonesia and Pivot FC Club. The data collection technique was carried out by measuring the futsal team of the University of Indonesia and Pivot FC with Purposive Sampling totaling 32 people. Aerobic capacity values are taken through a bleep test. The values of body mass index, body fat, and visceral fat are taken through the BIA (Bioelectric Impedance Analysis) method The data obtained is then processed and analyzed using SPSS. The results of the analysis using SPSS obtained an average VO2Max value of 36.64 / kg/minute while the average body mass index, body fat, and visceral fat respectively were 21.2, 14.2%, and 4.81. The results of the Spearman Rank correlation test (1) there is a correlation between body mass index and physical fitness of r = -0.471 and the significance of P-Value = 0.007 (2) there is a correlation between body fat and physical fitness of r = -391 and the significance of P-Value = 0.027 (3) there is a correlation between visceral fat and physical fitness of r = -409 and the significance of P-Value 0.020. The results of the analysis through UI showed that there was an inverse relationship with the value of body mass